Association between cardiometabolic index and cardiovascular disease: evidence From the NHANES 2007–2018 - Chen, Feiyu; Niu, Yongquan; Wu, Runzhe; Jiang, Haodong; Zhu, Jia; Wang, Congying; Xia, Xiaojun; Jin, Yunpeng (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAlthough the cardiometabolic index (CMI) has gained recognition as a new tool for evaluating metabolic health, the relationship between CMI and cardiovascular disease (CVD) remains unclear. This research sought to explore the potential association between CMI and CVD.MethodsParticipants from the 2007–2018 National Health and Nutrition Examination Survey (NHANES) were selected. Multivariable logistic regression analyses and smooth curve fitting were utilized to investigate this relationship, along with subgroup evaluations and interaction analyses.ResultsThis study included 12,837 subjects and the prevalence of CVD was 11.83%. After full adjustment, participants presenting with an increase of one unit in Ln-transformed CMI associated a 15% higher odds of CVD prevalence (OR = 1.15, 95% CI: 1.05–1.26). In the fully adjusted model, individuals falling into the highest CMI quartile (Quartile 4) demonstrated substantially 35% higher odds than those in the lowest CMI quartile (Quartile 1) (OR = 1.35, 95% CI: 1.11–1.66). In addition, there was no nonlinear relationship between CMI and CVD in our selected sample. This positive association was not greatly influenced by any of the stratifications.ConclusionsAmong US adults, having higher CMI levels is substantially associated with higher odds of CVD prevalence. This finding suggests that regular monitoring of CMI levels could enable physicians to initiate early interventions, potentially slowing the progression of CVD. However, in order to corroborate our findings, further prospective investigations are still required.